Islamic Banking Digital Marketing Strategy: Using Social Media and Content Marketing on Interest in Service Usage - Mohamad Rafii; Junaedi, Ahyar; Suratmoko, Bayu (International Journal of Entrepreneurship, Business and Creative Economy, 2025)
This study aims to analyze the effectiveness of digital marketing strategies in increasing consumer interest in Islamic banking services, focusing on the role of social media and content marketing. Using a quantitative approach, data was collected through a survey of 109 respondents who are customers of Bank Syariah Indonesia. The results of the analysis show that the use of social media significantly influences consumer awareness and emotional engagement, while informative and relevant content marketing builds trust and interest in Islamic banking products. Collectively, social media and content marketing can increase consumer interest in Islamic banking services by 84.6%. These findings show that digital marketing, through social media and content marketing, has a very important role in driving consumer interest in choosing and using Islamic banking services, and strengthening the position of Islamic banking in the global financial market.